Konstitusionalitas Hak Kesehatan Jiwa Warga Negara: Studi Kebijakan Penanggulangan Bunuh Diri di Kabupaten Gunungkidul - Enggar Wijayanto (Jurnal HAM, 2023)
The high suicide rate in Gunungkidul is quite high, causing the Regional Head to issue Regent Regulation Number 56/2018 as a policy to deal with suicide cases. This step is a concrete manifestation of dealing with and preventing massive suicides systematically. The average number, which reaches 20 to 30 cases every year, shows that suicide is no longer an individual problem, but has become a social-human tragedy. This research will discuss how the implementation of suicide prevention policies, as the role of the state in protecting the constitutional rights of citizens in the field of mental health, through an interdisciplinary approach as an integrated perspective to see the purpose of the law. This research is included in empirical research and uses a socio-legal approach. Data collection is obtained through primary data, including interviews, observations, documentation, and secondary data through the study of related literature. The results showed that in terms of effectiveness, the suicide prevention policy has not run optimally based on the comparison of suicide rates before and after the policy was enacted. Influencing factors include apparatus coordination, facilities, and social support. Besides that, the pandemic situation also has an effect. Conceptually and practically, the suicide prevention policy is an effort to uphold citizens' constitutional rights by strengthening the mental health aspects of the community by integrating formal and informal social control to achieve effective law according to its goals.